BEYOND GROWTH: HINDU RELIGIOUS PERSPECTIVES IN ECONOMY ETHICS AND ECONOMICS SUSTAINABLE - Ida Bagus Ngurah (Penelitian dan Pengembangan Ilmu, 2026)
Paradigm development economy that places growth product domestic gross (GDP) as indicator main success the more questionable because his inability to answer problem inequality social, degradation environment and quality welfare human beings. In line with development paradigm beyond growth, research This aim research for analyze relevance Hindu religious perspective in form ethical and sustainable economy​ as well as test connection the in a way empirical this research​ use approach quantitative with design explanatory and utilizing secondary data across regions that reflect Hindu religious values, behavior economy ethical, and indicators economy sustainable. Data analysis was carried out using path analysis for test influence direct and indirect direct between variables. Research results show that Hindu religious values are influential positive and significant to behavior economy ethical, and influential direct to economy sustainable. Besides that, behavior economy ethical proven mediate in a way significant connection between Hindu religious and economic values sustainable. This finding indicates that internalization Hindu values such as dharma, karma phala, and Tri Hita Karana play a role as informal institutions that form behavioral economics and improve quality development. This research contribution is theoretical for economic development, base values and paradigms beyond growth, and implications practical for formulation policy development, ethical and sustainable economy, in particular in context of public based Hindu culture. Keywords: beyond growth, Hinduism, economy ethica